Toward Precision Oncology in Ovarian Cancer: Dual PD-L1 and CD44 Biomarker Profiling for Recurrence Risk Assessment - Ebrahim, Noura A A; Eissa, Tamer S; Hussein, Mustafa A; Arafat, Aya; Amin, Nancy H (Asian Pacific Journal of Cancer Biology, 2025)
Background: Epithelial ovarian carcinoma (EOC) remains one of the most fatal gynecologic cancers, often presenting at an advanced stage and prone to frequent recurrence despite aggressive treatment. Identifying reliable prognostic biomarkers is essential for improving patient stratification and optimizing adjuvant treatment strategies. This study investigated the expression patterns of programmed death-ligand 1 (PD-L1) and CD44, a recognized cancer stem cell (CSC) marker, and examined their relationships with clinicopathological features, recurrence risk, and survival outcomes in EOC. Methods: A retrospective study was performed involving 90 patients with histologically confirmed EOC managed at National Cancer Institute, Cairo University. Immunohistochemistry was utilized to assess PD-L1 and CD44 expression in tumor samples. The associations between biomarker expression, clinical and pathological variables, recurrence-free survival (RFS), and overall survival (OS) were analyzed using Kaplan–Meier survival curves, multivariate logistic regression, and Cox proportional hazards models. Results: PD-L1 was expressed in 42.2% of tumors and showed significant associations with advanced International Federation of Gynecology and Obstetrics (FIGO) stage (p=0.017), higher tumor grade (p=0.004), presence of distant metastasis (p=0.002), and increased recurrence rates (p<0.001). CD44 positivity was identified in 71.1% of cases, predominantly among serous carcinoma subtypes (p=0.010), and was likewise linked to a higher recurrence risk (p<0.001). Patients with PD-L1-positive tumors exhibited a notably shorter median RFS compared to PD-L1-negative patients (31.3 vs. 54.7 months, p<0.001), as did CD44-positive individuals relative to their CD44-negative counterparts (36.3 vs. 56.7 months, p<0.001). Neither biomarker, however, demonstrated a statistically significant effect on OS during a median follow-up of approximately five years. Notably, patients with concurrent PD-L1 and CD44 expression experienced the poorest RFS outcomes (mean 30.9 months), while those negative for both markers showed the most favorable prognosis (mean 56.6 months, p<0.001). Multivariate analysis confirmed PD-L1 (OR 4.86, p=0.003) and CD44 (OR 9.61, p=0.006) as independent predictors of recurrence. Conclusions: The expression of PD-L1 and CD44 in EOC is independently associated with an elevated risk of disease recurrence, and their co-expression identifies a particularly high-risk patient subset. Although neither marker significantly influenced overall survival within the study’s follow-up period, their combined assessment holds promise for enhancing prognostic models and guiding the selection of patients for intensified monitoring and clinical trials exploring immune checkpoint blockade and CSC-targeted therapies.